Stress, Mindsets, and Success in Navy SEALs Special Warfare Training - Smith, Eric N.; Young, Michael D.; Crum, Alia J. (Frontiers in Psychology, 2020)
Mindsets can impact an individual’s performance in stressful experiences such as public speaking or receiving negative feedback. Yet we know little about the boundary conditions of where these mindsets predict success, and where they may become irrelevant or even maladaptive. The current research asks whether mindsets are beneficial in environments of extreme physical and mental stress using participants undergoing the notoriously challenging Navy SEALs training. We hypothesized that participants with stress-is-enhancing mindsets—who believe stress enhances their health, performance and wellbeing—will outperform those with stress-is-debilitating mindsets. In addition, we explore whether other mindsets about willpower and failure predict success in a similar manner. Following 174 Navy SEALs candidates, we find that—even in this extreme setting—stress-is-enhancing mindsets predict greater persistence through training, faster obstacle course times, and fewer negative evaluations from peers and instructors. We also find evidence that failure-is-enhancing mindsets may be detrimental to candidates' success, and nonlimited willpower mindsets prompt negative evaluations from others. Multiverse analyses were conducted to test for the robustness of these effects across researcher analytical decisions, which produced consistent results. We discuss how findings in this unique environment can provide insight into the importance of mindsets in other organizations and propose future avenues of research to further understand the causal role of mindsets in diverse workplace contexts.